Quality of Life and Psychopathology in Lichen Planus: A Neglected Disease Burden - Zeno Fiocco; Sophie Kupf; Leilah Patzak; Till Kämmerer; Teodora Pumnea; Lars E. French; Markus Reinholz (Medical Journals Sweden, 2021)
The disease burden of lichen planus and its impact on patients' quality of life have not been well studied. The aim of this mono-centre cross-sectional study was to investigate these factors. From June to September 2020, an anonymous survey was posted to 253 patients, who were diagnosed with lichen planus in our outpatient clinic from January 2018 to June 2020. Quality of life was evaluated using the Dermatology Life Quality Index (DLQI), the EuroQol 5-dimension 3-level score, and further quality of life indicators. Beck Depression Inventory II was used to evaluate symptoms of depression. A total of 100 patients completed and returned the survey. Lichen planus affected quality of life in 78% of cases. DLQI was higher for multiple localizations (r = 0.454, p < 0.001). Patients with genital lichen planus had a significantly higher DLQI (mean ± standard deviation (SD) 8.68 ± 6.96) than patients who were not affected in the genital area (5.01 ± 5.49; p = 0.009). DLQI was also significantly higher for ungual lichen planus (9.83 ± 7.6; not affected: 5.65 ± 5.84; p-value 0.039), and for cutaneous LP (mean 8.1, SD 6.22; not affected: 5.63 ± 6.12; p-value 0.045). Twenty-nine percent of patients had mild to moderate symptoms of depression, and 6% had severe symptoms of depression. Depression and reduced quality of life are an undetected and relevant burden affecting patients with lichen planus.